2023
DOI: 10.1371/journal.pone.0281899
|View full text |Cite
|
Sign up to set email alerts
|

Population-level median cycle threshold (Ct) values for asymptomatic COVID-19 cases can predict the trajectory of future cases

Abstract: Background Recent studies indicate that the population-level SARS-CoV-2 cycle threshold (Ct) values can inform the trajectory of the pandemic. The presented study investigates the potential of Ct values in predicting the future of COVID-19 cases. We also determined whether the presence of symptoms could change the correlation between Ct values and future cases. Methods We examined the individuals (n = 8660) that consulted different sample collection points of a private diagnostic center in Pakistan for COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Smaller studies have suggested that changes in Ct values can indicate changes in trajectory of the epidemic, including a study from Spain ( 33 ) that reported differential changes in mean Ct values and rate of positive tests in the first and second waves; a study from Pakistan ( 34 ), a study from Italy ( 35 ), and a study from Belgium ( 36 ) that reported a 17-day lag between changes in Ct values and positive tests, and a study from the United States that reported a 33-day lag between Ct values and cases ( 37 ). Our study, which used national surveillance data for >1 year, along with studies from ONS CIS and other studies in the United Kingdom ( 4 , 28 ) (A.S. Walker AS, unpub.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller studies have suggested that changes in Ct values can indicate changes in trajectory of the epidemic, including a study from Spain ( 33 ) that reported differential changes in mean Ct values and rate of positive tests in the first and second waves; a study from Pakistan ( 34 ), a study from Italy ( 35 ), and a study from Belgium ( 36 ) that reported a 17-day lag between changes in Ct values and positive tests, and a study from the United States that reported a 33-day lag between Ct values and cases ( 37 ). Our study, which used national surveillance data for >1 year, along with studies from ONS CIS and other studies in the United Kingdom ( 4 , 28 ) (A.S. Walker AS, unpub.…”
Section: Discussionmentioning
confidence: 99%